Analysis of the Development History and Problems of Sino-Russia Trade in the Context of "One Belt, One Road" - Chen, Xiao (International Journal of Global Economics and Management, 2024)
China and Russia, as neighboring economic powers, have geopolitical advantages and stable political relations. The two countries have complementary advantages in production factor endowment and industrial structure, creating favorable conditions for bilateral trade. This paper examines the healthy development momentum in China-Russia relations in recent years. For 13 consecutive years, China has been Russia's largest trading partner. However, the trade between the two countries is limited to low-value-added products and other issues, failing to reflect their comparative advantages fully. This paper analyzes the history and problems of Sino-Russia trade in the context of the 'Belt and Road' initiative. The content is divided into three parts. First, it introduces the background and reasons for the study. Secondly, the development of Sino-Russia trade is analyzed by taking the "Belt and Road" initiative as the dividing line. Finally, it analyzes the problems existing in the process of Sino-Russia trade development and puts forward suggestions.